Inhibition of STAT3 phosphorylation attenuates impairments in learning and memory in 5XFAD mice, an animal model of Alzheimer's disease - Moonseok Choi; Hyunju Kim; Eun-Jeong Yang; Hye-Sun Kim (Elsevier, 2020)
The pathophysiological roles of astrocytes in the reactive state are thought to have important significance in the pathogenesis of neurodegenerative diseases, including Alzheimer's disease (AD). However, the detailed mechanisms underlying the transition of astrocytes from the resting state to the reactive state during neurodegenerative disease largely remain to be defined. Here, we investigated the pathways involved in activating astrocytes from the resting state to the reactive state in primary cultured astrocytes treated with oligomeric Aβ and in the hippocampus of 5XFAD mice. Treatment with oligomeric Aβ induced an increase in reactive astrocytes, as assessed by the protein level of glial fibrillary acidic protein (GFAP) and this increase was caused by STAT3 phosphorylation in primary cultured astrocytes. The administration of Stattic, an inhibitor of STAT3, rescued the activation of astrocytes in primary cultured astrocytes and in the hippocampus of 6-month-old 5XFAD mice as well as impairments in learning and memory. Collectively, these results demonstrated that reactive astrocytes in the AD brain are induced via STAT3 and the impairments in learning and memory observed in 5XFAD mice are rescued by STAT3 inhibition, suggesting that the inhibition of STAT3 phosphorylation in astrocytes may be a novel therapeutic target for cognitive impairment in AD.